Finding the contemporary in the traditional: reassessing the impact of indigenous Maya and modern western pedagogies on identity and self (Educação e Pesquisa, 2015)
This work contrasts what is taught and learned – other than what is intended – in different educative settings and two historical eras. In a comparison of ethnographic studies conducted in the US and in Guatemala, it compares the “hidden curriculum” (KOHLBERG, 1975) of formal western schooling – the norms, values and practices that are conveyed by the content knowledge taught, and the interaction patterns, assessment procedures and participation structures used (PHILLIPS, 1983) – with similar structures in an indigenous Maya community in Guatemala. It analyzes what children learn, the impact on their identities, and how those types of learning connect to future social and occupational destinations. Educational settings differ in the types of learning and teaching they support; they produce different kinds of learners with different identities and goals. It has been argued that modern schooling actually interferes with the values and practices of so-called traditional cultures, leading to the abandonment of traditional languages, practices and beliefs. Such an argument denies the flexibility of traditional cultures, relegating them to a static “present” not characteristic of the dynamic identities actually being constructed in the 21st century. Conversely, we argue that traditional pedagogies can protect enduring cultural identity (SPINDLER, G; SPINDLER, L, 2000) and lead to more successful accommodation to modernity (RUDOLPH, L; RUDOLPH, S, 1984). We connect this argument with research exploring myths about what schooling can and cannot do to achieve social mobility and improved societal conditions.